Time to non-persistence of sodium-glucose co-transporter 2 inhibitors and its prognostic factors among patients with type 2 diabetes in Universiti Malaya Medical Centre - Sofian, Nurul Farhana Mohd (2024)
Introduction: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have emerged as a new guideline-directed medical therapy (GDMT) for managing cardiovascular-kidney-metabolic (CKM) syndrome. Understanding the pattern of SGLT2i treatment persistence can help prevent unwarranted non-persistence of this GDMT and simultaneously, develop interventions to mitigate its negative consequences. This study aimed to evaluate the treatment persistence time on SGLT2i and to identify the prognostic factors for SGLT2i persistence time among adults with type 2 diabetes (T2D) at the Universiti Malaya Medical Centre, Kuala Lumpur, Malaysia. Methods: This was a retrospective cohort study involving adults aged 18 years and above with T2D who were initiated with SGLT2i between January 2016 and December 2021. The study outcome was time to SGLT2i non-persistence, defined as the time to first 90-day gap after the estimated end date of pharmacy supply. Kaplan-Meier estimate was used for median SGLT2i persistence time, life table analysis was used for obtaining persistence rates and Cox Proportional Hazard regression was used to identify the prognostic factors for the time to treatment persistence. Results: This study involved 602 adults with T2D, with the majority being male (52.0%). The mean age of patients was 60.1 years (standard deviation (SD) = 10.7). The median treatment persistence time was 40.5 months (95% confidence interval (CI): 34.6, 54.0). Treatment persistence rates reduced from 94.5% at 6 months to 78.0% at 1 year, and 62.7% at 2 years. Patients with baseline estimated glomerular filtration rate (eGFR) <60 ml/min/1.73m2 had an adjusted hazard ratio (AHR) of 1.57 (95% CI 1.20, 2.04; p = 0.001) for non-persistence of SGLT2i, compared to those with eGFR ≥60 ml/min/1.73m2. The use of DPP4i had an AHR of 0.75 (95% CI 0.57, 0.98; p = 0.042) for non-persistence of SGLT2i. Conclusions: Half of the patients discontinued SGLT2i within 3.5 years. Those with baseline eGFR <60 ml/min/1.73m2 and without concomitant DPP4i use were significantly associated with SGLT2i non-persistence. This study provides valuable insights into the time to SGLT2i non-persistence in adults with T2D and the underlying factors to facilitate more personalised diabetes management to optimise health outcomes.